Population-Based Case-Control Study Assessing the Association between Statins Use and Pulmonary Tuberculosis in Taiwan - Liao, Kuan-Fu; Lin, Cheng-Li; Lai, Shih-Wei (Frontiers in Pharmacology, 2017)
Background and Objectives. Little evidence is available about the relationship between statins use and pulmonary tuberculosis in Taiwan. The aim of the study was to explore this issue. Methods. Using the database of the Taiwan National Health Insurance Program, we conducted a population-based case-control study to identify 8236 subjects aged 20 years and older with newly diagnosed pulmonary tuberculosis from 2000 to 2013 as the cases. We randomly selected 8236 sex-matched and age-matched subjects without pulmonary tuberculosis as the controls. Subjects who had at least one prescription of statins before the index date were defined as “ever use”. Subjects who never had one prescription of statins before the index date were defined as “never use”. The odds ratio (OR) and 95% confidence interval (CI) for pulmonary tuberculosis associated with statins use was estimated by a multivariable logistic regression model. Results. After adjustment for co-variables, the adjusted OR of pulmonary tuberculosis was 0.67 for subjects with ever use of statins (95% CI 0.59, 0.75). In a sub-analysis, the adjusted ORs of pulmonary tuberculosis were 0.87 (95% CI 0.69, 1.10) for subjects with cumulative duration of statins use < 3 months, 0.77 (95% CI 0.58, 1.03) for 3-6 months, and 0.59 (95% CI 0.51, 0.68) for ≥ 6 months, compared with subjects with never use of statins. Conclusions. Statins use correlates with a small but statistically significant risk reduction of pulmonary tuberculosis. The protective effect is stronger for longer duration of statins use. Due to a case-control design, a causal-relationship cannot be established in our study. A prospective cohort design is needed to confirm our findings.